Determination of Maturity and reproductive cycle of Small Spotted Catshark Scyliorhinus canicula (Linnaeus, 1758)(Scyliorhinidae: Elasmobranchii) From the Syrian marine water - Ali, Malek Fares; Saad, Adib Saad; Kurbaj, Haitham Kurbaj; Jneidi, Shadi Jneidi (Iraqi Journal of Aquaculture, 2022)
This study was carried out in the Marine Sciences Laboratory of Agriculture Faculty at Tishreen University, in collaboration with the Higher Commission for Scientific Research, on the Small Spotted Catshark Scyliorhinus canicula (Linnaeus, 1758) in the Syrian marine water (Eastern Levant of Mediterranean sea); From Rass Albassit northward ( 35° 55  N), to the Lebanese borders southward (°34 50´ N). During the period January 2012 to September 2013. 417 specimens (231 females, 186males) were collected at depths 50-250 m, from sandy or sandy-muddy bottoms by different fishing gears; mainly hook sub bottom. S. canicula suffers an overfishing into the Syrian marine water. The highest fishing quantity was during spring and summer. The total length of specimens ranged from 225 to 515 mm TL, and weighed from 22 - 380 g. Smallest specimens matured of males and females were 355, 350 mm, respectively. The total length ranged from 355 -500 mm TL for adult males, and 350 -515 mm TL for adult females. S. canicula is an oviparous species. The largest yolky oocytes diameter was 12 mm, and weighed 1.3 g. The ripe oocytes is covered and ovulated as an egg capsule. The length of egg capsules ranged from 42 -50 mm, their width from 16-18 mm, and their mass reached to 4.8 g.